The quality of life of older adults acutely admitted to the emergency department: A cross‐sectional study - Mette Elkjær; Jette Primdahl; Christian B. Mogensen; Mikkel Brabrand; Bibi Gram (Wiley, 2022)
Abstract Aim To investigate perceptions of individual QoL among acutely admitted older adults and explore whether homecare and readmission were associated with QoL. Design A cross‐sectional study at three Danish Emergency Departments. Methods Semi‐structured interviews, using the Schedule for the Evaluation of Individual Quality of Life - Direct Weighting (SEIQol‐DW) (range 0-100) with patients ≥65 years, were conducted from August 2018 to July 2019. The differences between patients receiving homecare (yes/no) and readmission (yes/no) were tested using linear regression analyses with bootstrap procedures. Results Overall, we included 406 patients, of whom 38% received homecare. The mean SEIQoL‐DW‐score was 76 (SD = 19). The most important areas of individual QoL were Family, Social activities, Health, Everyday life and Leisure activities. Receiving homecare was associated to a significantly lower QoL score: −8 (SE = 2) and a significantly lower score in the categories Family and Health. There was no association between readmission and QoL.